Globalisation - Challenges for Health and Health System - Westaway, Jennifer (School of Business Law, Curtin Business School, Curtin University of Technology, 2012)
This paper examines the challenge that globalisation poses to health and to health systems. Globalisation has generated significant challenges throughout the world, not the least of which is the ease with which economic risk can be transmitted. One area which has only recently received academic attention is the impact of this risk on health and health systems. This paper argues that health is a progressively realised right, and that because the right to health lacks the protection of a global legal or regulatory structure, with competing and conflicting demands created by the effects of globalised industry, trade, and labour movements, health budgets will become increasingly marginalised. As a consequence the right to health as recognised by a number of international instruments is rendered nugatory. The paper argues that because of the tension between globalisation and health policy issues relating to the prioritisation of health spending, health spending must be considered in light of the concept of health as a human right if the widening in the inequities between the health of rich and poor is to be addressed.